PERAN MAHASISWA PENDIDIKAN AGAMA ISLAM DALAM MENGUATKAN MODERASI BERAGAMA DI ERA DIGITAL - Badriyah, Fatikhatul (Fakultas Agama Islam Universitas Islam Madura, 2024)
The digital era is when people can communicate through a medium so close even though they are far from each other. In the era of digitalization like today, the digital space has become an arena for contests and competitions. This point is what causes irresponsible groups to use it as a place to launch their missions, nourish conflicts, create content that benefits them, and even become impromptu ustadz by creating religious content textually without filtering to cause conflicts among others. Religious moderation in Indonesia is how we change our religious mindset to be moderate. Students as part of society and also agents of change commonly called agents of change have a big task in terms of strengthening religious moderation. This article aims to determine the role of Islamic religious education students in the digital era in strengthening religious moderation. This article aims to determine the role of Islamic religious education students in the digital era in strengthening religious moderation. The preparation of this article uses a qualitative type approach. The data collection technique was carried out through literature studies which were then analyzed with descriptive analysis. It was found that there is a role for Islamic religious education students in strengthening religious moderation in the digital era, namely by creating articles and religious content that are attractively packaged and then uploading them to social media sites. Through the writing of this article, it is hoped that Islamic religious education students can take advantage of their potential so that they can strengthen religious moderation in the digital era.